Defiant school choice? Educational freedom, access, and Arkansas’s AP African American studies controversy - Morris, Sarah Ruth; Maranto, Robert (Frontiers in Education, 2024)
On August 11, 2023, the Arkansas Department of Education (ADE) notified schools just before the fall semester's start that they would no longer support the college-board-approved AP African American Studies (APAAS) course. Subsequently, all five districts offering the course declared their intent to proceed despite the lack of state funding and course credits. We conduct a document and qualitative thematic analysis in this mixed methods study. In documents, we find distinctive shifts in how the significance of APAAS is portrayed within differing contexts. Using interviews with Arkansas superintendents, teachers, students, and stakeholders, we find four major interview themes: the role of education in preserving democratic values, equity concerns, the significance of community support and advocacy, and the impact of political influences. Documents and stakeholders interviewed perceive the ADE's withdrawal of support as politically motivated, while superintendents, teachers, and students are primarily motivated by the curriculum, student welfare, and community interests in offering APAAS. We conclude by suggesting that greater consideration of factual knowledge, coupled with choice within and between schools, could defuse such controversies.